Social Networking in Library and Information Services:Current Scenario - Ansari, Aslam; Nazim, Mohd. (Journal of Information and Knowledge, 2016)
Social Networking (SN) began from late 20th Century and is growing up rapidly. It works as a medium of communication with one to another for sharing their experiences and information regarding their interest, and also helps to build up longtime relationship between individuals and groups. In the field of LIS services, it may help to promote the services of LIC (Library and Information Centers). This study provides the efficient account of SN tools and how it affects communication with others. The findings disclose that some SN tools are gaining popularity among LIS professionals as they use at least one of Social Networking Sites (SNS). The most active professionals are from younger generation between the age group of 26-35 years. The professionals opine that SNS is very effective to deliver the services of LIC.